2011
DOI: 10.1021/bc2000066
|View full text |Cite
|
Sign up to set email alerts
|

Bioconjugation of l-3,4-Dihydroxyphenylalanine Containing Protein with a Polysaccharide

Abstract: We describe the simple bioconjugation strategy in combination of periodate chemistry and unnatural amino acid incorporation. The residue specific incorporation of 3,4-dihydroxy-l-phenylalanine can alter the properties of protein to conjugate into the polymers. The homogeneously modified protein will yield quinone residues that are covalently conjugated to nucleophilic groups of the amino polysaccharide. This novel approach holds great promise for widespread use to prepare protein conjugates and synthetic biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…Indeed, the concept was successfully employed in some typical protein engineering studies based on canonical amino acid mediated substitution mutagenesis [19], [20], [21]. We also demonstrated that the concept could be applied to non-canonical amino acid mediated protein engineering approach [22], which permitted the generation of functional proteins with unnatural properties efficiently [23], [24].…”
Section: Introductionmentioning
confidence: 83%
“…Indeed, the concept was successfully employed in some typical protein engineering studies based on canonical amino acid mediated substitution mutagenesis [19], [20], [21]. We also demonstrated that the concept could be applied to non-canonical amino acid mediated protein engineering approach [22], which permitted the generation of functional proteins with unnatural properties efficiently [23], [24].…”
Section: Introductionmentioning
confidence: 83%
“…Similarly, 3,4-dihydroxy-L-phenylalanine (L-DOPA, Fig. 2 (10)) can be oxidized by NaIO 4 to form a nucleophile-reactive orthoquinone intermediate [72].…”
Section: Bioorthogonal Labeling Of Proteinsmentioning
confidence: 99%
“…Protein purification, quantification, and fluorescence analysis Purification and quantification of the recombinant proteins were performed as described by Ayyadurai et al (2011b). Fluorescence analysis was carried out with 2 lM protein by exciting at 470 nm, and the emission maximum was recorded using a spectrofluorimeter equipped with digital software.…”
Section: Chemicalsmentioning
confidence: 99%